2019
DOI: 10.1111/pai.13088
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ocular and nasopharyngeal microbiome in allergic rhinoconjunctivitis

Abstract: Background Allergic rhinoconjunctivitis (ARC) is a prevalent allergic condition in the pediatric population. Microbial dysbiosis has increasingly been recognized to influence on host immunity and allergic diseases. However, the microbial profile of ARC has not been characterized. This cross‐sectional study aims to evaluate the changes in nasal and ocular surface microbiome of children with ARC. Methods Ocular and nasopharyngeal swabs were collected from controls and pediatric ARC cases for 16S rRNA amplicon se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 36 publications
2
26
0
1
Order By: Relevance
“…At the phylum level, previous studies also consistently indicated that the microbial flora colonizing the OS was dominated by Proteobacteria, Actinobacteria , and Firmicutes . 11 , 15 , 37 39 Among the dominant genera (> 1%), the detection of Pseudomonas, Corynebacterium, Streptococcus , and Staphylococcus was consistent with the study of Ge et al 13 In an earlier study, researchers reported that Pseudomonas, Corynebacterium, Staphylococcus, Streptococcus, and Acinetobacter represented the “core genera” in the healthy conjunctival microbiome. 38 In our study, these genera were shared by at least 50% of HC subjects.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…At the phylum level, previous studies also consistently indicated that the microbial flora colonizing the OS was dominated by Proteobacteria, Actinobacteria , and Firmicutes . 11 , 15 , 37 39 Among the dominant genera (> 1%), the detection of Pseudomonas, Corynebacterium, Streptococcus , and Staphylococcus was consistent with the study of Ge et al 13 In an earlier study, researchers reported that Pseudomonas, Corynebacterium, Staphylococcus, Streptococcus, and Acinetobacter represented the “core genera” in the healthy conjunctival microbiome. 38 In our study, these genera were shared by at least 50% of HC subjects.…”
Section: Discussionsupporting
confidence: 85%
“…Although the composition of the ocular microbiome is still under dispute, data have become available to indicate the distribution characteristics of OS microbial communities in health and disease states. Recent studies have demonstrated the potential relationship between changes in the OS microbiome and some conditions, such as trachoma, 11 fungal keratitis, 12,13 ulcerative bacterial keratitis, 14 conjunctivitis, 15 dry eye, 16 mesangial gland dysfunction, 17,18 blepharitis, 19 and contact lens wearing. 20,21 However, all of these studies were based on 16S rRNA gene sequencing, which, despite contributing to understanding the potential diversity of the OS bacterial flora, has limited ability to characterize nonbacterial components and functional profiles of the OS microbiome.…”
mentioning
confidence: 99%
“…Differences based on seasonality can also be attributed to allergy. A negative correlation between ocular surface microbiome diversity and allergy severity was found in one publication of allergic rhinoconjunctivitis patients (Table 1) (Yau et al 2019). Research on the impact of ocular surface diseases on the eye microbiome is still in its infancy and needs to be validated (Table 1).…”
Section: Discussionmentioning
confidence: 90%
“…Both Firmicutes and Bacteroidetes account for a variable but smaller part. In the paediatric population (Butcher et al 2017; Cavuoto et al 2018; Yau et al 2019), the prevalence of phyla is similar to the adult population (p > 0.01, paired t ‐test). B, Ocular surface microbiome results based on geographic location (≥18 yo).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation